And most of us go Pro in something other than Sports Hiring Preferences and their Effect on the Labor Market for Collegiate Football Players - Mario Lackner (Johannes Kepler University of Linz, Department of Economics, 2010)
This paper analyzes the labor market for collegiate football players and argues that professional football teams have discriminating preferences when making their hiring decisions. An empirical analysis of panel data of 32 NFL teams in recent seasons is carried out to test the effects of such preferences on the performance of teams. The results provide strong evidence that certain criteria, which do have a high influence on a players chances to start a career in Professional Football, have actually little influence on team-efficiency whatsoever. Consequently, this implies that discrimination in the form of hiring preferences create a sub-optimal result in terms of building a team, as well as for the overall labor market in Professional Football.
Keywords: J7; J2; L83; C23; 330; Labor market in sports; discrimination in hiring; production efficiency; stochastic production frontier; Sportler; Hochschule; Kündigung; Arbeitsmarktdiskriminierung; Professioneller Sport; USA